Model Pemberian Punishment dan Reward dalam Penanaman Kedisiplinan Siswa Kelas 4 Sekolah Dasar - Audrine Yohand Shalsa Bila; Anatri Desstya (Universitas Negeri Padang, 2023)
This research aims to describe the science learning process in instilling discipline through giving punishment and rewards to fourth-grade elementary school students. The data used is qualitative, obtained from observation, interviews and documentation. Data sources involve teachers and students. Data collection techniques through observation, interviews and documentation. The data analysis technique used consists of data reduction stages, data presentation, and drawing conclusions. Test the validity of the data using triangulation of sources and methods. The results of the research are that in the implementation of giving punishment and rewards to student discipline, 95.45% of the data on teacher discipline was obtained, and 85% of the data on instilling student discipline. This is characterized by the teacher's activities at the beginning of planning preparation, saying hello and praying, giving motivation, repeating the material, and explaining the objectives, the core of learning is conditioning students and explaining the material, students observing and listening, giving questions and assignments, giving prizes to students, giving punishment for violators, closing the lesson summarizing the material and reflection, checking the neatness and cleanliness of the class, and praying and playing guessing games. Thus, giving punishment and rewards is successful in instilling students' disciplinary attitudes